The Influence of Social Media Marketing, Online Customer Review, and E-SERVQUAL to Purchase Decision through Trust (Bekam Therapy Center Jember) - Anindya Restu Permana; Toni Herlambang; Abadi Sanosra; Nursaid Nursaid (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This study examines the positive and significant effect of social media marketing, online customer reviews, and e-SERVQUAL on purchase decisions through trust. This study is quantitative research. The whole population is Bekam Therapy Center’s customers. The sample is 104 customers. The data collection method was carried out by distributing questionnaires online. WarpPLS 7.0 was used as a data analysis method to identify and estimate the relationship between variables. The variables consist of social media marketing (X1), online customer review (X2), e-SERVQUAL (X3), purchase decision (Y), and trust (Z). The result shows that; 1) Social media marketing does not have a direct positive effect on purchase decisions but does influence trust, 2) Online customer reviews positively affect purchase decisions and trust, 3) E-SERVQUAL has a significant positive effect on both purchase decisions and trust, 4) Trust significantly influences purchase decisions. 5) The mediating role of trust is evident in the relationship between social media marketing and purchase decisions, and e-SERVQUAL and purchase decisions, but not between online customer reviews and purchase decisions.